Analysis of the Implementation of the School Operational Assistance Program at the State Junior High School 1 Taliwang, West Sumbawa Regency - Saputra, Aan Endaniyar; Suparman, Suparman; Junaedi, Junaedi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research discusses a thesis on the Analysis of the Implementation of the School Operational Assistance Program in State Junior High School 1 Taliwang, West Sumbawa Regency. The objectives of this research are as follows : 1. To explain the process of implementing the School Operational Assistance Program in State Junior High School 1 Taliwang, West Sumbawa Regency. 2. To describe the impact of implementing the School Operational Assistance Program in State Junior High School 1 Taliwang, West Sumbawa Regency. 3. To identify the supporting and inhibiting factors in the implementation of the School Operational Assistance Program in State Junior High School 1 Taliwang, West Sumbawa Regency. The research method used for this study is a qualitative research design. Qualitative research is a research approach that uses a scientific background to interpret phenomena and is conducted by involving various available methods. The study involved 1 headmaster of State Junior High School 1 Taliwang, 1 BOS fund treasurer, 2 teachers, and 2 parents. Data collection procedures included interviews and documentation, with data analysis using qualitative descriptive analysisThe implementation of the BOS program at State Junior High School 1 Taliwang was carried out in accordance with the BOS guidelines outlined in the Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 63 of 2022 regarding the Technical Guidelines for School Operational Assistance. Additionally, State Junior High School 1 Taliwang was considered transparent in terms of receiving and using BOS funds. This transparency was evident through information boards displaying BOS fund receipts for each semester throughout the year and BOS fund expenditures for each semester over the year.As a result of this research, it can be concluded that the process of implementing the BOS program at State Junior High School 1 Taliwang is fairly effective, despite several challenges in its implementation.